2022
DOI: 10.1155/2022/7514898
|View full text |Cite|
|
Sign up to set email alerts
|

Spiral CT Image Characteristics and Differential Diagnosis Secondary Pulmonary Tuberculosis and Lung Cancer Based on Visual Sensors

Abstract: Helical CT plain scan has high spatial and area resolution, which is beneficial to the extraction of CT features of pulmonary nodules, and is of great significance for the diagnosis and differential diagnosis of pulmonary diseases. In order to deeply study the role of visual sensor image algorithm in CT image, this paper adopts clinical simulation method, data fusion method, and image acquisition method to collect images, analyze CT image features, and simplify the algorithm and create a CT model that can bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…With multislice spiral CT scanning technology, the outlines of lung tissue and lesions are clearly displayed. However, the missed diagnosis rate is relatively high when multislice spiral CT scanning is used for early screening of central lung cancer [ 8 ]. With the progress in the screening of groups with a high risk of thoracic disease, benign nodules have been detected in a large number of patients.…”
Section: Introductionmentioning
confidence: 99%
“…With multislice spiral CT scanning technology, the outlines of lung tissue and lesions are clearly displayed. However, the missed diagnosis rate is relatively high when multislice spiral CT scanning is used for early screening of central lung cancer [ 8 ]. With the progress in the screening of groups with a high risk of thoracic disease, benign nodules have been detected in a large number of patients.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%